Clothing fibers - Learning Seed Company (Chicago, Ill. : Learning Seed, 2008)
A clothing & textiles 101 overview of the elements of fabric, this curriculum-based program introduces students to the primary types of fibers and the basic differences between natural and synthetic fibers
Title from title screen
Teaching guide for this program is availabke at www.learningseed.com
DVD Format
With English subtitle
Keywords: Textile fibers; Textile fabrics